FORMULATION AND CHARACTERISATION OF SUSTAINED RELEASE MICROBEADS LOADED WITH ZALTOPROFEN - KIRAN, H. C.; VENKATESH, DHANDAPANI NAGASAMY; RAJESH KUMAR, RAMAN (International Journal of Applied Pharmaceutics, 2019)
Objective: The main aim of the present investigation was to formulate and evaluate microbeads of zaltoprofen. Zaltoprofen, a BCS class II drug used in the treatment of rheumatoid arthritis. Zaltoprofen has a shorter half-life of 2.8 h, and it is administered at a dose of 80 mg thrice a day. By encapsulating the drug into microbeads, it is expected that the release of the drug would be prolonged and thereby, it reduces the frequency of administration and better patient compliance may be improved. Methods: Gellan-chitosan and calcium chloride beads of zaltoprofen were prepared employing ionotropic gelation method using different concentrations of gellan, chitosan, calcium chloride and zaltoprofen. The microbeads were evaluated for its various Physico-chemical parameters such as particle size determination, drug entrapment efficiency, infrared spectroscopy study, differential scanning calorimetry, X-ray diffraction analysis, scanning electron microscopy, in vitro drug release study and in vivo oral bioavailability studies. Results: The results suggested that the batch FG-II exhibited higher drug entrapment efficiency (72.42±0.013), a sustained drug release for a period of 24 h. The pharmacokinetic profile of the drug from microbeads exhibited an enhanced oral bioavailability (2.4 times higher than that of pure drug), lower elimination rate (1.14 times lesser for the drug in microbeads) with prolonged elimination half-life (2.561 times higher than pure zaltoprofen). Conclusion: Zaltoprofen entrapped microbeads demonstrated as a better delivery system for the sustained release of drug and also to circumvent the drawbacks associated with conventional therapy.